Disciplinary Matters in the Hypatia Controversy - Mitra, Namrata (Atlantis)

(untitled) (Mount Saint Vincent University, 2018)
The problem that was thrown up during the Hypatia controversy is a systemic one. I argue that objections to Tuvel's essay regarding its exclusion of perspectives from marginalized points of view should be re-framed as a disciplinary wide issue. I show some ways in which the universal applicability and vantage point often assumed in canonical writings in philosophy, specifically on history and personal identity, emerge from specific contexts and points of view. I demonstrate what is at stake in recognizing the particularity of these contexts. I find that the false dichotomy between seemingly interested “Social justice” scholarship and disinterested inquiries into truth, which I hold perpetuates the disciplinary conditions that produced the Hypatia controversy.